Multifunctional magnetoliposomes as drug delivery vehicles for the potential treatment of Parkinson’s disease - Cifuentes, Javier; Cifuentes-Almanza, Santiago; Ruiz Puentes, Paola; Quezada, Valentina; González Barrios, Andrés Fernando; Calderón-Peláez, María-Angélica; Velandia-Romero, Myriam Lucia; Rafat, Marjan; Muñoz-Camargo, Carolina; Albarracín, Sonia L.; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder after Alzheimer’s disease. Therefore, development of novel technologies and strategies to treat PD is a global health priority. Current treatments include administration of Levodopa, monoamine oxidase inhibitors, catechol-O-methyltransferase inhibitors, and anticholinergic drugs. However, the effective release of these molecules, due to the limited bioavailability, is a major challenge for the treatment of PD. As a strategy to solve this challenge, in this study we developed a novel multifunctional magnetic and redox-stimuli responsive drug delivery system, based on the magnetite nanoparticles functionalized with the high-performance translocating protein OmpA and encapsulated into soy lecithin liposomes. The obtained multifunctional magnetoliposomes (MLPs) were tested in neuroblastoma, glioblastoma, primary human and rat astrocytes, blood brain barrier rat endothelial cells, primary mouse microvascular endothelial cells, and in a PD-induced cellular model. MLPs demonstrated excellent performance in biocompatibility assays, including hemocompatibility, platelet aggregation, cytocompatibility, mitochondrial membrane potential and intracellular ROS production. Additionally, the nanovehicles showed acceptable cell internalization and endosomal escape abilities. Moreover, molecular dynamics simulations were employed to better understand the underlaying translocating mechanism of the OmpA protein. Overall, the versatility and the notable in vitro performance of this novel nanovehicle make it a suitable and promising drug delivery technology for the potential treatment of PD.